Stegosatyrus, a new genus of Euptychiina from the grasslands of neotropical realm (Lepidoptera: Nymphalidae: Satyrinae) - Zacca, Thamara; Mielke, Olaf H. H.; Pyrcz, Tomasz W.; Casagrande, Mirna M.; Freitas, André V. L.; Boyer, Pierre (Zootaxa, 2013)
Three species of Pampasatyrus Hayward, 1953 (Satyrinae, Pronophilina) are transferred to Stegosatyrus n. gen. (Eupty-chiina) based on morphological evidence: S. imbrialis (Weeks, 1901) n. comb. from Bolivia (Cochabamba) and northern Argentina; S. ocelloides (Schaus, 1902) n. comb. from Paraguay (Hernandarias and Caaguazú) and Brazil (Midwest, Southeast and South regions); and S. periphas (Godart, [1824]) n. comb. from southern Brazil, northeastern Argentina (Buenos Aires) and Uruguay. A new species is described, Stegosatyrus hemiclara Pyrcz, Boyer & Zacca, n. sp. from the Andes of southern Peru. The neotype of Satyrus periphas Godart, [1824] and the lectotypes of Epinephele imbrialis We-eks, 1901 and Euptychia ocelloides Schaus, 1902 are designated. Redescriptions and illustrations are presented, including information on geographical and temporal distribution, and habitats. The oviposition process, eggs and first instars of S. periphas are published for the first time.